Commensal Urinary Lactobacilli Inhibit Major Uropathogens In Vitro With Heterogeneity at Species and Strain Level - Johnson, James A.; Delaney, Lydia F.; Ojha, Vaishali; Rudraraju, Medha; Hintze, Kaylie R.; Siddiqui, Nazema Y.; Sysoeva, Tatyana A. (Frontiers in Cellular and Infection Microbiology, 2022)
The human urinary microbiome is thought to affect the development and progression of urinary tract infections (UTI), particularly recurrent UTIs in aging populations of women. To understand the possible interactions of urinary pathogens with commensal bacteria inhabiting the aging bladder, we conducted an initial functional assessment of a representative set of urinary lactobacilli that dominate this niche in postmenopausal women. We created a repository of urinary bladder bacteria isolated via Enhanced Quantitative Urinary Culture (EQUC) from healthy postmenopausal women, as well as those with culture-proven recurrent UTI diagnosis. This repository contains lactobacilli strains from eight different species. As many other lactobacilli are known to inhibit human pathogens, including typical uropathogens, we screened the urinary lactobacilli in our repository for their ability to inhibit model uropathogens in vitro. We observed that many urinary lactobacilli strongly inhibit model strains of gram-negative Escherichia coli and Klebsiella pneumoniae but demonstrate less inhibition of gram-positive Enterococcus faecalis. The observed inhibition is not specific to model uropathogens and also affects clinical and multidrug-resistant isolates. Our preliminary analysis of inhibition mechanisms implicates pH as an important factor with additional cell-dependent inhibition mechanisms that differ amongst species and strains of urinary lactobacilli. Overall, our data show that urinary lactobacilli are broadly inhibiting uropathogen growth in vitro via a combination of different mechanisms. Nevertheless, simple measured inhibition level is not predictive of health outcomes in colonized patients, and species and strain level diversity of urinary lactobacilli is high.